Reimbursement of pharmacogenetic tests at a tertiary academic medical center in the United States - Lemke, Lauren K.; Alam, Benish; Williams, Roy; Starostik, Petr; Cavallari, Larisa H.; Cicali, Emily J.; Wiisanen, Kristin (Frontiers in Pharmacology, 2023)
Introduction: Pharmacogenetics (PGx) has the potential to improve health outcomes but cost of testing is a barrier for equitable access. Reimbursement by insurance providers may lessen the financial burden for patients, but the extent to which PGx claims are covered in clinical practice has not been well-characterized in the literature.Methods: A retrospective analysis of outpatient claims submitted to payers for PGx tests from 1/1/2019 through 12/31/2021 was performed. A reimbursement rate was calculated and compared across specific test types (e.g., single genes, panel), payers, indication, and the year the claim was submitted.Results: A total of 1,039 outpatient claims for PGx testing were analyzed. The overall reimbursement rate was 46% and ranged from 36-48% across payers. PGx panels were reimbursed at a significantly higher rate than single gene tests (74% vs 43%, p<0.001).